Thailand's animals in peril: a systematic review of microplastic contamination and its ecological consequences - Weerachon Sawangproh; Paiphan Paejaroen (Environmental Sciences Europe)
Abstract Microplastic (MP) pollution is a critical environmental issue affecting ecosystems globally, with significant implications for wildlife and human health. This systematic review examines MP contamination in animal taxa across Thailand from 2016 to 2024, highlighting the extensive presence of MPs in diverse habitats, particularly in benthic environments, which account for 55% of contamination. Fish, especially from the Cyprinidae family, are the most affected, followed by filter feeders like mussels and shrimp. The review identifies prevalent MP types, including polyethylene (PE), polypropylene (PP), and polyester (PES), with fibers being the dominant shape. The ingestion of MPs poses direct physical threats to wildlife and serves as a vector for harmful chemicals, raising concerns about bioaccumulation and biomagnification within food webs, ultimately impacting human health through seafood consumption. Despite increasing research activity, significant knowledge gaps remain regarding the long-term ecological and health effects of MP pollution. Future research should focus on the physiological impacts of MP ingestion, the dynamics of trophic transfer, and the effectiveness of waste management strategies. Enhanced detection methods and assessments of regional and seasonal variability in MP contamination are essential for a comprehensive understanding of this issue. Addressing MP pollution in Thailand necessitates a multidisciplinary approach that combines scientific inquiry, public awareness, and effective policy implementation. This review underscores the urgent need for targeted mitigation strategies to protect biodiversity and human health from the pervasive impacts of MP contamination.